PENGARUH FASILITAS KERJA DAN KOMPETENSI TERHADAP KEPUASAN KERJA PEGAWAI DAN DAMPAKNYA TERHADAP KINERJA PEGAWAI KANTOR KELURAHAN SEKECAMATAN MUARA BULIAN KABUPATEN BATANG HARI - Budi Darma; Arna Suryani; Yunan Surono (Universitas Batanghari, 2018)
This study raised concerns about the effect of working facilities and competencies to job satisfaction and its impact on performance. The research was conducted within the scope of the District Muara Bulian precisely on the entire village.The performance of employees is among the key issues are constantly faced by the organization management. Therefore, among the tasks of the manager is a very important move employees to contribute to the success of the organization. The purpose of this study is to examine and determine the influence of working facilities, competencies, job satisfaction and performance. Influence of working facilities, competencies, job satisfaction and employee performance tested either directly or indirectly.To examine issues directly above the survey conducted by distributing questionnaires to employees village office. The results of the questionnaire were analyzed qualitatively and verification. Data analysis tool made by using Path Analysis. The results of this study indicate that the working facilities and competence have an influence on job satisfaction and have an impact on performance, both directly and indirectly.